DAMPAK KEBERADAAN PABRIK PENGOLAHAN KELAPA SAWIT (PKS) PT. KARYA ABADI SAMA SEJATI (KASS) TERHADAP SOSIAL EKONOMI MASYARAKAT DI SEKITAR KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Agusniarty '; Susy Edwina; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this research in not to know the effect of PKS to the social condition and economic society but also to describe the condition of social community before and after the existance of PKS PT. KaryaAbadiSamaSejati in the District of Pujud. This research used the survey method with the cluster sampling to the technique to the 73 sample of 278 populations that consist of 52 respondents of employees and 21 respondents of non employees. The analysis that is used focussed on the development of people, manpower, income and ratio of the bail. The system of people development after and before the existence of PKS that doesn’t still give big impact with the change about 3%, while at the level of manpower doesn’t still give impact and it can be looked from the decrease of the working participation about -39,5%  and the increas of the jobless about 10,37%. The average of income per month of the employees respondent after the existance of PKS increas about 25,79%  is Rp1.365.385,00 to Rp2.021.230,00 and the average of income per year after the theexistance of PKS respondent about 41,72% is Rp8.249.961,00 to Rp11.691.730,00, and the average of income per mounth of the non employees income respondent after the existence of PKS increas about 11,71% is Rp2.364.286,00 to Rp2.641.190,00 and the average  of income per year after the existance of PKS about 15,93%is Rp10.381.857,00 to Rp12.035.714,00. The ratio of bail shows the high value that is 52,81%. The condition of social community has been a change where there is a change of genetic relationship region to be dispersed because of the activity factor, occure the social problem is disagreements and misunderstanding between citizen and new comer. Keywords: Social and economic impact, Pabrik Kelapa Sawit (PKS)